Organisation of Territory Restoration Activities Following a Natural Disaster - Helešicová, Barbora; Nováková, Jana; Marvan, Petr; Hromádka, Vít (Elsevier B.V, 2024)
Natural disasters are unfrequent, but inevitable parts of life. This article addresses this topic and at the same time proposes a methodology for managing the restoration of the territory affected by natural disasters. The application of this methodology is presented using a case study dealing with the restoration of a municipally owned building in the Czech Republic damaged by a tornado. This is the first recorded natural disaster of this kind in the area under study, which resulted in the necessity to pay attention to new approaches to the restoration of the affected territory. The project management tools were chosen in accordance with common construction practice, the originality lies mainly in the incorporation of the methods used into the actual process of the affected territory restoration which places special demand on its course in terms of organization, time, financial and decision-making processes. The outputs presented in this paper are designed to help municipal authorities manage the restoration of damaged buildings quickly and efficiently.

Natural disasters are unfrequent, but inevitable parts of life. This article addresses this topic and at the same time proposes a methodology for managing the restoration of the territory affected by natural disasters. The application of this methodology is presented using a case study dealing with the restoration of a municipally owned building in the Czech Republic damaged by a tornado. This is the first recorded natural disaster of this kind in the area under study, which resulted in the necessity to pay attention to new approaches to the restoration of the affected territory. The project management tools were chosen in accordance with common construction practice, the originality lies mainly in the incorporation of the methods used into the actual process of the affected territory restoration which places special demand on its course in terms of organization, time, financial and decision-making processes. The outputs presented in this paper are designed to help municipal authorities manage the restoration of damaged buildings quickly and efficiently.
Organisation of Territory Restoration Activities Following a Natural Disaster
Keywords: project management; work breakdown structure (WBS); organigram; responsibility assignment matrix; natural disaster; time schedule; project management; work breakdown structure (WBS); organigram; responsibility assignment matrix; natural disaster; time schedule